1994
DOI: 10.1017/s1352465800013084
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Applications of the REHAB Assessment System

Abstract: In the last 10 years, as part of the push towards greater community provision of services for the psychiatrically disabled in the UK, assessment has assumed a prominent position. A variety of different assessment instruments have been employed, including assessment of patient attitudes and opinions, of the environment, social networks and basic living skills (Carson, 1991; TAPS, 1992). Amongst the differing assessment types, behaviour rating scales have a distinct contribution. They are particularly applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…Observation of behaviour within the normal regime of the day hospital was carried out by two members of staff working at the day hospital by using REHAB (Baker & Hall, 1983), a widely used rating form originally designed to assess change in long-stay psychiatric patients (Ruud, Martinsen, & Friis, 1998). It has been successfully used before with large samples of elderly mentally ill patients (Baker & Hall, 1994;Carson, Patrick, & Shaw, 1989;Nichol, 1989). Carson et al (1989) found the inter-rater reliability to be .80 for the General Behaviour subscale and .77 for the Deviant Behaviour subscale for the elderly mentally ill population.…”
Section: Methodsmentioning
confidence: 99%
“…Observation of behaviour within the normal regime of the day hospital was carried out by two members of staff working at the day hospital by using REHAB (Baker & Hall, 1983), a widely used rating form originally designed to assess change in long-stay psychiatric patients (Ruud, Martinsen, & Friis, 1998). It has been successfully used before with large samples of elderly mentally ill patients (Baker & Hall, 1994;Carson, Patrick, & Shaw, 1989;Nichol, 1989). Carson et al (1989) found the inter-rater reliability to be .80 for the General Behaviour subscale and .77 for the Deviant Behaviour subscale for the elderly mentally ill population.…”
Section: Methodsmentioning
confidence: 99%
“…In order to permit sufficient change to be detected and to increase the sensitivity of the scale in general, a 10-point visual analogue format similar to that of the phobic rating scale of Marks and Mathews [60] and the REHAB questionnaire of Baker and Hall [61,62] was used. Five attitudinal anchor statements joined by dotted lines were placed under a visual analogue line to orient respondents (completely disagree, disagree, in between, agree, and completely agree).…”
Section: Scale Constructionmentioning
confidence: 99%
“…The most fully researched tool for such ideographic measurement is probably the Personal Questionnaire (Chalkley & Mulhall, 1991;Shapiro, 1961). As this can be cumbersome to administer, the visualanalogue line method of recording used by Baker and Hall (1994) in their observational evaluation package, Rehabilitation Evaluation Hall and Baker Scale (REHAB), was employed as a compromise. This measure consisted of two separate forms, one for 'before intervention' and one for 'after intervention'.…”
Section: Goal Settingmentioning
confidence: 99%